Masses and Widths of Resonances for the Cornell Potential - M. N. Sergeenko (Advances in High Energy Physics)
Physical properties of the Cornell potential in the complex-mass scheme are investigated. Two exact asymptotic solutions of relativistic wave equation for the coulombic and linear components of the potential are used to derive the resonance complex-mass formula. The centered masses and total widths of the leading